PERENCANAAN LANSKAP PEKARANGAN DENGAN SISTEM PERTANIAN TERPADU - Mardiyanto, Anggi; Pramukanto, Qodarian; Mugnisjah, Wahju Qamara (http://arl-faperta.ipb.ac.id/, 2014)
Home gardens (pekarangan) constitute the potential land to be utilized as productive agricultural land due to their proximity with the people’s house, so that the management of these land is easy. Residents of Teluk Waru hamlet have not optimally utilized their home garden. For optimizing the production of pekarangan, an integrated agricultural landscape was made, with the concept of LEISA and is expected to be able to fulfill monthly appropriate livelihood need (KHL) for residents of Teluk Waru hamlet. In the efforts of optimizing the pekarangan utilization, two alternatives of agribusiness were planned. Lansdcape planning of Pekarangan with integrated farming system concept in the resident’s home garden of Teluk Waru hamlet with land size of 350 m2 showed the following results of agribusiness financial feasibilities: alternative 1 showed NPV of Rp 45.261.784,00, IRR of 111%, and Net B/C of 3,49. Agribusiness of alternative 1 was feasible to be run because of having NPV > 0, IRR above interest rate of 20 % and Net B/C > 1. Analysis results of financial feasibility of alternative 2 agribusiness showed NPV of Rp 72.128.612,00, IRR of 137%, and Net B/C of 4,28. Agribusiness of alternative 2 was feasible to be run because of having NPV > 0, IRR above interest rate of 20 % and Net B/C > 1. In order that the monthly livelihood needs of the famers are fulfilled, the agribusiness of alternative 1 and alternative 2 need minimum land size of 175,57 m2 and 123,82 m2 respectively.